Is primary prevention accessible to students? - Milošević Georgiev, Andrijana; Neškov, Lea; Nikić, Sonja; Obradović, Dragiša; Marinović, Valentina; Odalović, Marina; Krajnović, Dušanka (Archives of Pharmacy, 2025)
The college years are critical to students' health as they face various challenges, including social influences and unhealthy lifestyles. Limited access to health services in residence halls increases the risk of unhealthy behaviours. The aim of this study was to investigate students' attitudes towards public health services for primary prevention in dormitories and to make suggestions for improvement. A cross-sectional study was conducted using a questionnaire among students living in halls of residence. The survey explored students' views on healthcare and the availability of preventive services for students living away from home. A total of 996 students participated (response rate 99.1%). Most were unemployed (83.9%). The most frequent preventive visits were to dentists (34.4% twice a year, 24.7% once a year), while 37.7% never visited a gynaecologist/urologist. The majority (68.6%) stated that a pharmacy was necessary in their dormitories. Basic health services include general practitioners (82.3%) and psychologists (21.4%). Attitudes towards health centres varied significantly by place of residence (p
Keywords: primary prevention; student population; pharmacy services; public health services